SUSTAINABILITY OF OPERATION ELEMENT SECOND NAVAL COMMAND FLEET IN INDONESIAN WORD SHIPS DEGREES TO SUPPORT THE NAVAL TASK - Tri Sumarsono; Budi Santoso; Sutrisno Sutrisno; Priyadi Hartoko (Indonesian Naval Technology College - Sekolah Tinggi Teknologi Angkatan Laut - STTAL, 2022)
The sustainability degree of operation of the KRI elements in Koarmada II is determined by the interrelated influences and interactions between one aspect and another as a very complex system arrangement, so a comprehensive analysis is needed regarding the sustainability of the KRI operation title in terms of aspects of geography, politics of defense and security, the Financial/Budget aspect of the Indonesian Navy and the Physical/Technical aspect of the KRI. In order to be able to see the sustainability value of the KRI operation title, a dynamic model was developed that could determine the projected KRI operational title sustainability value with a time dimension of up to 40 years in the future. In this Thesis, the researcher developed a model with a system dynamic model approach which was integrated with the Analytical Hierarchy Process (AHP) method to obtain the sustainability value of the KRI operations title in this case the KRI Koarmaa II operation title based on aspects of Geography, Defense and Security Politics, Financial/Navy Budget aspects and KRI Physical/Technical aspects. From the results of the formulation and simulation of the model with the System Dynamic approach to the sustainability of the KRI Koarmada II element operations. After the model was run for 40 years, the value of the Geopolhankam aspect was at index 5.00, which means